Synopsis of the terrestrial Reptiles of Equatorial Guinea - Sánchez-Vialas, Alberto; Calvo-Revuelta, Marta; Riva, Ignacio De La (Zootaxa, 2022)
We present a comprehensive catalogue of the reptiles of Equatorial Guinea, consisting of 118 species belonging to 67 genera and 22 families. There are two species of Crocodylia, ten of Testudines and 106 of Squamata; this last taxon is represented by 62 species of snakes, two amphisbaenians and 42 lizards. Of these 118 species, seven are present only in Annobon, seven only in Bioko, 47 only in Río Muni, 53 occur both in Bioko and Río Muni (or Bioko, Río Muni and other islands), and four are sea turtles. Despite its high diversity, the level of endemism of Bioko is relatively low, with only four endemic species out of the 60 species reported for the island. In contrast, despite its low diversity, Annobon has the highest endemicity level, with five endemic species (and two introduced). No endemic species are known for the rest of the regions of Equatorial Guinea, which contain 100 species. We reveal several new country and species records, and point to some pending taxonomic questions to be addressed. Among the new species records, we highlight the presence of Cyclanorbis elegans, which represents the most meridional known population of the genus. Additional species are expected to be found in Equatorial Guinea as further field and taxonomic work is developed.